Female genital tuberculosis: About 6 cases - Asma Hmila; HafsaTaheri; Saadi Hanane; Ahmed Mimouni (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: Genital tuberculosis in women is uncommon. Its clinical pictures and radiological aspects are nonspecific. The histological confirmation is necessary. Treatment is medical but infertility prognosis is often poor due to irreversible tubal damages. Objective: Our study aims to report the epidemiological characteristics of genital tuberculosis suffering women, their clinical pictures and the treatment undertaken. Methods: This is a retrospective study reporting six cases of confirmed genital tuberculosis operated in the Obstetrics and Gynecology Department of the Mohammed VI university hospital in Oujda between January 2015 and December 2018. Results: The profile of the woman carrying this disease in our study was that of the young woman in the period of genital activity with an age average of 36 years. Low socioeconomic level was found in all the patients. The major clinical signs were pelvic pain, abdominal distension, and weight loss. The radiological images found were essentially cystic with ascites. Exploration laparoscopy found pseudo-tumoral masses, whitish granulations, and adhesions. The confirmation of the diagnosis is histological represented by epithelio-gigantocellular follicles with or without caseous necrosis. Under a well-conducted antibacillary medical treatment for a sufficient duration, the evolution is favorable with a risk of sequels especially on the patient's fertility. Conclusion: The most important treatment of tuberculosis is preventive based on the BCG vaccine and the improvement of living conditions. Genital tuberculosis in women isn't frequent but has a poor prognosis especially the fertility one. Medical treatment is effective but tubal damages can be irreversible.